Perception of music-induced emotions in patients with somatoform disorders compared to healthy controls. (July 2019) - Firle, Carl; Teufel, Martin; Blumenstock, Gunnar; Smolka, Robert; Erschens, Rebecca; Windthorst, Petra; Zipfel, Stephan; Junne, Florian
Although music therapy has become a widespread approach used in the multimodal treatment of psychosomatic disorders, this is the first study investigating the perception of music-induced emotions (PoMIE) in patients with somatoform disorders. For the purposes of this study, n = 23 patients (PG) with somatoform disorder (F45) were assessed for PoMIE within an experimental design. Additionally, n = 25 healthy controls were included as a control group (CG) matched for age and gender. A questionnaire including the dimensional (valence, arousal) and the discrete (basic emotions) model were applied to assess PoMIE. At t0, the PG gave lower ratings of the emotion happiness, F (1, 48) = 1.24, p < .01, than the CG. Significantly higher ratings of fear were observed in the PG than in the CG. At t1, the PG gave higher ratings of happiness for happy-targeted music stimuli than at t0, t (22) = 2.35, p < .05. Higher ratings of fear in the PG compared to the CG also persisted after inpatient therapy, t (46) = −2.48, p < .05. The results suggest a lower perception of happiness and a higher perception of fear in the PG. A multimodal, inpatient therapy seems to influence the happiness perception of music-induced emotions in PG. The results may inform the further evaluation of music therapy interventions.